Atypical hematological manifestation of celiac disease: A case report of aplastic anemia in a 2‐year‐old child and review of the literature - Thea vonGraffenried; Mattia Rizzi; Michel Russo; Andreas Nydegger; Simon Kayemba‐Kay's (Wiley, 2021)
ABSTRACT Introduction Celiac disease typically presents with symptoms of malabsorption, but extraintestinal manifestations are increasingly reported. Aplastic anemia as the mode of celiac disease presentation is extremely rare in children. Case presentation We report a 2‐year‐old boy who presented with loose stools, loss of appetite, and bicytopenia with severe aregenerative normocytic anemia. Investigations, including bone marrow aspirate and biopsy, revealed aplastic anemia. Screening for malabsorption showed increased plasma concentrations of anti‐transglutaminase and anti‐gliadin antibodies. A duodenal biopsy confirmed the histologic features of celiac disease. The child received a packed red cell transfusion and was started on a gluten‐free diet, with a very good prognosis and normalization of both his blood and histological parameters. To the best of our knowledge, our report is the sixth pediatric case in the literature. Conclusion Screening for celiac disease should be performed in children with unexplained hematological abnormalities such as aplastic anemia with or without gastrointestinal symptoms.